Peran Entrepreneurship Dalam Memajukan Perekonomian Indonesia - Susila Andriyati; Shinta Deanova Chareunnisa; Zathu Restie Utamie (J-EBI: Jurnal Ekonomi Bisnis Islam, 2023)
This study aims to: 1). Provide a new perspective on entrepreneurship studies and its relation to the progress of the Indonesian economy. 2). Provide evaluation materials to stakeholders so that entrepreneurship can contribute to the progress of the Indonesian economy. The method in this research is library research be- cause the object of research can only be answered through library research. This study uses qualitative data and secondary data sources. The results of this study indicate that entrepreneurship plays a role in dynamizing the economic activities of families, communities, regional and state-owned companies. The number of entrepreneurs in Indonesia is still small compared to its population, therefore efforts to increase the number of entrepreneurs must continue. There are four factors that need to be considered in the devel- opment of entrepreneurship, namely: access to capital, the role of innovation, entrepreneurship training and the role of the government in creating a good business climate. Facts show that entrepreneurs play a major role in improving the quality of life of individuals, communities and countries. Entrepreneurship is also one of the determinants for creating a prosperous society and country.